The neural processing of sentences in bilinguals and monolinguals: an fMRI study of portugues-english bilinguals and portuguese monolinguals reading comprehension effects on brain activation - Bailer, Cyntia (2016)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2016.